A case study of a formative assessment practice and the effects on students' self-regulated learning. (March 2021) - Granberg, Carina; Palm, Torulf; Palmberg, Björn
Highlights: The formative assessment practice had a large effect on students' perceived autonomy. The practice also had a large effect on students' self-efficacy. Students started using more SRL skills at higher developmental levels in all SRL phases. The formative assessment practice involved innovative strategies to support students' SRL. The practice was both teacher-centered and student-centered. Abstract: The study investigates one mathematics teacher's implementation of formative assessment and its effects on students' self-regulated learning (SRL). A questionnaire administered before and after the eight-month long intervention shows a significant effect, compared to two control classes, on students' motivational beliefs involved in SRL. Qualitative data shows a notable enhancement of the students' SRL behavior in the classroom. Analysis of the teacher's implemented formative assessment shows a practice integrating several aspects of formative assessment, and provides empirical evidence of what formative assessment with large effects on students' SRL may look like and how it fits with models of SRL development.